Dual-Energy Spectral Computed Tomography: Comparing True and Virtual Non Contrast Enhanced Images - Širůčková, Kateřina; Marcoň, Petr; Dostál, Marek; Širůčková, Anna; Dohnal, Přemysl (Measurement Science Review, 2022)
Spectral computed tomography (CT) imaging is one of several image reconstruction techniques based on the use of dual-layer CT. The intensity and attenuation of the radiation are measured in relation to different wavelengths, and such a procedure results in complex three-dimensional (3D) imaging and (pseudo) color adjustment of the soft tissue. This paper compares true non-contrast (TNC) enhanced images with virtual non-contrast (VNC) enhanced ones. Virtual native images are acquired by means of spectral computed tomography, and it has been suggested that VNCs could potentially substitute real native images to reduce significantly the total radiation dose from multiphase spectral CT. A comparison was performed by defining certain parameters that represent the difference between the measured and the calculated values in the images. The parameters included the mean value and standard deviation of the computed tomography number, signal-to-noise ratio (SNR), and contrast-to-noise ratio (CNR). All of these items were analyzed via statistical tests using p-value. The results are interpreted and correlated with those presented by other authors, who, however, did not make an examination on a comprehensive basis - five tissues simultaneously by using a single device. Prospectively, if analogies were found between the two types of images, it would be possible to skip the TNC image, thus markedly reducing the radiation dose for the patient.